Predictive value of late gadolinium enhancement cardiovascular magnetic resonance in patients with persistent atrial fibrillation: dual-centre validation of a standardized method. Issue 1 (29th December 2022) - Althoff, Till F; Eichenlaub, Martin; Padilla-Cueto, David; Lehrmann, Heiko; Garre, Paz; Schoechlin, Simon; Ferro, Elisenda; Invers, Eric; Ruile, Philipp; Hein, Manuel; Schlett, Christopher; Figueras i Ventura, Rosa M; et al.
Abstract: Aims: With recurrence rates up to 50% after pulmonary vein isolation (PVI) in persistent atrial fibrillation (AF), predictive tools to improve patient selection are needed. Patient selection based on left atrial late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) has been proposed previously (UTAH-classification). However, this approach has not been widely established, in part owed to the lack of standardization of the LGE quantification method. We have recently established a standardized LGE-CMR method enabling reproducible LGE-quantification. Here, the ability of this method to predict outcome after PVI was evaluated. Methods and results: This dual-centre study ( n = 219) consists of a prospective derivation cohort ( n = 37, all persistent AF) and an external validation cohort ( n = 182; 66 persistent, 116 paroxysmal AF). All patients received an LGE-CMR prior to first-time PVI-only ablation. LGE was quantified based on the signal-intensity-ratio relative to the blood pool, applying a uniform LGE-defining threshold of >1.2. In patients with persistent AF in the derivation cohort, left atrial LGE-extent above a cut-off value of 12% was found to best predict relevant low-voltage substrate (≥2 cm two with <0.5 mV during sinus rhythm) and arrhythmia-free survival 12 months post-PVI. When applied to the external validation cohort, this cut-off value was also predictive of arrhythmia-free survival for both, the total cohort and the subgroup with persistent AF (LGE < 12%: 80% and 76%; LGE > 12%: 55% and 44%; P = 0.007 and P = 0.029, respectively). Conclusion: This dual-centre study established and validated a standardized, reproducible LGE-CMR method discriminating PVI responders from non-responders, which may improve choice of therapeutic approach or ablation strategy for patients with persistent AF. Graphical Abstract: Graphical abstract Risk stratification of patients with persistent AF based on the individual extent of left atrial late gadolinium enhancement. In the derivation cohort (University Heart Center Freiburg, Germany), a cut-off value of 12% LA LGE was found to best discriminate between responders and non-responders to catheter ablation (PVI only). Application of this cut-off value to LGE-CMR performed in the validation cohort ( n = 182, 36% paroxysmal AF, Hospital Clínic, University of Barcelona), confirmed its predictive value with equal discriminating power in patients with persistent AF. Shown are three-dimensional left atrial LGE-CMR reconstructions (postero-anterior view) with colour-coding based on LGE (blue: image intensity ratio ≤1.2; yellow: image intensity ratio >1.2; red: image intensity ratio ≤1.32). AF, atrial fibrillation; LA, left atrial; LGE, late gadolinium enhancement; PVI, pulmonary vein isolation; CMR, cardiac magnetic resonance.